2021
DOI: 10.1177/15330338211036528
|View full text |Cite
|
Sign up to set email alerts
|

The Cancers-Specific Survival of Metastatic Pulmonary Carcinoids and Sites of Distant Metastasis: A Population-Based Study

Abstract: Background: Lung cancer is the leading cause of cancer-related deaths and pulmonary carcinoids (PCs) account for almost 2% of all pulmonary malignancies. However, few published articles have reported prognosis and related factors of pulmonary carcinoid patients. Material and Method: The Surveillance, Epidemiology, and End Results (SEER) database was used to collect data of patients diagnosed with metastatic PCs from 2010 to 2016. The prognosis and survival of these patients were compared by employing Cox propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…23 This difference between the present study and that reported by Zhang et al may be explained by a lack of power of our study, but also because the study reported by Zhang et al was not designed to specifically evaluate the impact of surgery on OS, in including a multiplicity of comparisons. 23 As reported herein, patients in the operative and nonoperative groups were different by definition;…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…23 This difference between the present study and that reported by Zhang et al may be explained by a lack of power of our study, but also because the study reported by Zhang et al was not designed to specifically evaluate the impact of surgery on OS, in including a multiplicity of comparisons. 23 As reported herein, patients in the operative and nonoperative groups were different by definition;…”
Section: Discussioncontrasting
confidence: 65%
“…The OS was significantly higher in the operative group, but this benefit was not significantly higher after multivariate analysis and adjustment on confounding factors, as was found for metastatic pancreatic and small intestinal NETs elsewhere 17–19 . However, in the study reported by Zhang et al, including 1763 patients from the US SEER database, surgery for metastatic L‐NETs was a factor associated with good prognosis in terms of cancer‐specific survival in univariate and multivariate analysis 23 . This difference between the present study and that reported by Zhang et al may be explained by a lack of power of our study, but also because the study reported by Zhang et al was not designed to specifically evaluate the impact of surgery on OS, in including a multiplicity of comparisons 23 .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations